Microbiological profile of foods marketed in the state of Pernambuco - Rodrigues, Jefferson Renan Pinheiro; Albuquerque, Krause Gonçalves Silveira; da Costa, Matheus Antonio; Vasconcelos, Guilherme de Oliveira Araujo; da Silva, Thiago Filipe; de Lima Santos, Jessica Karolina; da Silva, Ivini Ferreira; Freitas, Samuel Rodrigues do Nascimento (Seven Editora, 2023)
Food security is essential because it is directly related to human health and well-being. When food is contaminated by bacteria, fungi, parasites, chemicals or foreign bodies, it can cause a range of illnesses, from mild food poisoning to serious illnesses that can lead to death. Foodborne illnesses (EDDs) arising from the consumption of such contaminated food are substantially relevant to public health. Its occurrence systematically triggers damages to various spheres of society, including the economic sector, due to absenteeism, compromise of trade and depletion of industrial activities. Thus, food hygiene, in recent years, has been the subject of increasing interest. Objective: To review the literature regarding the microbiological profile of foods marketed in the state of Pernambuco. Literature Review:  Regarding the bacterial profile, the studies included in this review identified contamination in the samples in the following proportions: fecal coliforms (20%), Salmonella (55%), Escherichia coli (72%), Staphylococcus genus (71%), Listeria monocytogenes (25%). Regarding the mycological profile, contamination by Aspergillus flavus (70%), Penicillium (60%), Fusarium (80%), Aspergillus parasitic us (80%) was identified. In addition, bacterial and fungal toxins were identified in 65% of the samples. Final considerations: The presence of different bacteria and fungi with pathogenic potential, in addition to their toxins, in foods marketed in Pernambuco reflect the importance of promoting good food handling practices as a preventive strategy for DTA.DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-091